Pemanfaatan Cagar Budaya di Kabupaten Pacitan sebagai Media Penunjang Pendidikan Sejarah - Blasius Suprapta (Jurnal Pendidikan Sejarah Indonesia, 2018)
The cultural heritage of Pacitan Regency is concentrated in Punung area. Most of the cultural heritage Punung is a prehistoric cultural heritage, consisting of paleolitik sites, mesolitik and neolitik sites. Paleolithic sites are widespread throughout Kali Baksoka, while the mesolithic sites include the residential cave sites Song Terus, Song Keplek and Song Gupuh. The neolithic sites include among others Ngrijangan neolithic workshop and Ngrijangan Sengon. Some of these sites have been designated as a cultural heritage and can be used as a medium for educational support. Paleolitik Kali Baksoka cultural heritage sites can be used as supporting media of paleolithic cultural level, cultural site of Song Terus and Song Keplek as a medium of life support of mesolitic cultural level and cultural heritage of Ngrijangan site as supporting life of neolithic culture level.DOI: http://dx.doi.org/10.17977/um033v1i12018085